Traditional and ankle-specific vertical jumps as strength-power indicators for maximal sprint acceleration - Nagahara, R.; Naito, H.; Miyashiro, K.; Morin, J.-B.; Zushi, K. (The Journal of Sports Medicine and Physical Fitness, 2014)
AIM: This study aimed to determine the demand of strength-power capabilities represented by traditional and ankle-specific vertical jump modalities - squat jump (SJ), counter-movement jump (CMJ), rebound-continuous jump (RJ), rebound-continuous ankle jump (AJ) - relative to sprint acceleration ability during the entire acceleration phase of maximal sprint. METHODS: Nineteen male sprinters performed a 60-m maximal sprint and various vertical jumps. Correlation coefficients among the vertical jump performances and between those and the 60-m sprint time and sprint acceleration at each step were calculated. RESULTS: There were significant relationships between the 60-m sprint time and SJ height, CMJ height, AJ height, and AJ index. AJ height and index had no correlation with any other jump variables. Acceleration was significantly correlated with SJ height from the 6th to the 10th steps (r=0.48-0.51) and with CMJ height from the 5th to the 11th steps (r=0.46-0.54). Acceleration was also correlated with the AJ index from the 14th to the 19th steps (r=0.48-0.54). Acceleration had no correlation with the RJ index at any step. CONCLUSION: The results suggest that the AJ allows assessment of different reactive strengths compared with traditional jump modalities. To accelerate effectively, the explosive strengths of the SJ and CMJ are important during the early stage of acceleration (from 6.6±0.4 to 17.5±0.8 m), and the reactive strength represented by the AJ is necessary during the later stage of acceleration (from 23.4±1.0 to 33.7±1.4 m). Sprinters and coaches should be aware of the different demands of strength-power capability for effective acceleration.